The brake pressure depends upon the pedal ratio - Lotte, Julia Sophie; Luuk, Daan Sem; Max, Sven Noah; Nick, Alexander Simon (International research journal of management, IT and social sciences, 2019)
The brake disc having a factor of safety (FOS) within the range of 2 to 3 is sustainable. The disc with a FOS less than 2 or greater than 3 undergoes distortion and are less sustainable. Theoretically it has been proven using graphs and calculations that a slight variation in the pedal ratio leads to a large variation in the clamping forces and stopping distance. As per the comparisons made from the FOS and as per result from Ansys, when the pedal force is 1200N and the pedal ratios are 7.2and 4.5, the FOS are 2.1 and 2.8 respectively. Hence the disc is sustainable. When the pedal force is 1500N, and the pedal ratio is 4.5, the FOS is 2.2. Hence in this case too, the disc is sustainable. Therefore by maintaining proper pedal ratios, the length of the pedal can be made compact and with effective braking effects. This phenomenon is useful in case of racing vehicles as it reduces the effort of driver. The proper pedal design work also determines the size of master cylinder to be adopted for the vehicle.